tHE INTERNATIONALIZATION OF THE I+D AS ADVANTAGE COMPETITIVE OF THE COMPANIES AND THE ENTERPRISING - Seclen Luna, Jean Paúl (2009)
Acquiring and integrating knowledge from geographically dispersed locations, companies can generate more innovation, more value and lower cost. However, the relationship between diversity and geographical knowledge is important, but not always immediately obvious. Therefore, finding new niches of knowledge of value in order to foster innovation is similar to prospecting for gold. Moreover, the entrepreneur plays a major role in the development of a region or country.